Associations of autoantibodies and clinical profile of the patients with systemic sclerosis. Issue 3 (21st September 2022) - Mahmud, Shahin; Choudhury, Minhaj R.; Bandhan, Iftekhar H.; Islam, Md. Sahidul; Shahin, Md. Abu; Haq, Syed A.; Zaman, Mohammad M.
Abstract: Background: Systemic sclerosis is characterized by the involvement of organs and the presence of specific antibodies. The objectives of this study were to identify the autoantibodies and to determine their association with the selected clinical features of the disease among Bangladeshi systemic sclerosis patients. Methods: This cross‐sectional study was performed at the rheumatology outpatient clinic of Bangabandhu Sheikh Mujib Medical University. Autoantibodies against nine systemic sclerosis‐specific antigens were tested using an enzyme‐linked immunoassay immunoblot kit. Several clinical features of patients with positive and negative autoantibody were examined by χ 2 or Fisher's exact tests. Results: A total of 71 patients with systemic sclerosis (66; 93.0% female) were included. Their mean age at disease onset was 33.2 years. Fifty‐seven (80.3%) patients had diffuse cutaneous subtype. Out of nine autoantibodies, four were positive, anti‐topoisomerase‐I (57.7%), anti‐U1 ribonucleic protein (21.1%), anti‐RNA polymerase III (18.3%), and anticentromere antibodies (4.2%). Eleven (15.5%) patients were negative for any antibodies and 11 patients were positive for at least two autoantibodies. Anti‐U3‐RNP, anti‐PM‐Scl, anti‐Ku, and anti‐Th/To auto antibodies were absent in all patients. Anti‐RNA polymerase III was associated with raised pulmonary arterial systolic pressure (PASP) and anti‐U1‐RNP with decreased forced vital capacity (FVC). Conclusions: Anti‐topoisomerase‐I was the commonest autoantibody in patients with systemic sclerosis in Bangladesh. Anti‐RNA polymerase III antibody had  significant association with raised PASP and anti‐U1‐RNP with decreased FVC. Abstract : Autoantibodies and their distribution in patients with systemic sclerosis. Key points: Anti‐topoisomerase‐I was the most prevalent autoantibody in patients with systemic sclerosis in Bangladesh. Coexistence of antiribonucleic acid polymerase‐III and anti‐U1‐ribonucleoprotein was a common finding. Antiribonucleic acid polymerase‐III antibody and anti‐U1‐ribonucleoprotein had significant associations with pulmonary arterial hypertension and restrictive lung disease, respectively.